Enhanced surface finishing of bearing raceways - Knight, Peter (Cranfield University, 2000)
Bearing surfaces are highly engineered and high precision parts in regard to surface finish, waviness, form and dimensional size. Surface finishing techniques will not only affect the surface finish and texture but the mechanical properties of the surface and subsurface including surface stress state and hardness as well as chemical properties. The bearing surface is a functional surface influencing fatigue, wear, and friction, noise and lubrication regime. Bearings are low cost, high volume commodity products, which adds additional constraints to any manufacturing process of low cost, fast cycle time and automation. This thesis documents the development route for a superfinishing technique for bearing raceways. Initially work was performed on electrochemical machining (ECM) of raceways, but this was found to improve the surface finish too slowly and gave poor waviness as a result of non-conductive MnS inclusions becoming exposed on the bearing surface during ECM. Abrasive honing stones or superfinishing tapes were then combined with the ECM, a process called electrofinishing to remove these MnS peaks. A beneficial interaction between the ECM and the abrasive resulted in reduced loading of the abrasive and therefore more aggressive cutting and for longer. Using a fine grit (3- 4 pm) CBN vitreous bonded honing stone the surface finish of a ground ring (0.3 pm Ra) or a turned surface (1.2 pm Ra) could be improved to <0.02 pm Ra in around 6 seconds. These new surfaces showed low Rtm and Aq (slope), but also acceptable or very good levels of waviness. The material removal is dominated by the ECM process while the rate of surface finishing is controlled by the abrasive process. The process of electrofinishing gives the possibility of fast, high and controlled material removal capability combined with fine surface finishing, which presently must be achieved by throughfeed honing or two stage honing. The main difficulty to overcome is achieving a stable consistent honing needed for a production process. These difficulties arise from the incompatibility of the ECM electrolyte and honing fluid (usually an oil). Improvements were made by using a water soluble synthetic metalworking fluid mixed with the NaN03 electrolyte. Further improvements are possible by better choice of honing stone, better application of stones, while for superfinishing tapes, the use of tape feed and oscillation will give further improvements.